Turkish water projects in the Tigris and Euphrates .. Goals and intentions - حداد حامد عبيد (Journal of Economics and Administrative Sciences, 2012)
Turkey Consider Tigris and Euphrates rivers as a national rivers, and not an a International rivers, so that . It insists on its absolute sovereignty on that resources. The block ( levee ) which Turkey established should not create International problems. The All International agreements and laws in this sect warrant the rights of all the states that located in river stream to use it without any consider to the regional absolute right. During the 1980s, Turkey construct water projects, started with GAP, project which is one of the greatest project in the world, in spite of the plane of construct of the keep an levee on the Euphrates was pre of that project. The GAP includes, thirteen main projects, from which. There are seven projects on the Euphrates, and sex projects on the Tigris. In addition, the project includes. Set up twenty-two levee with eighteenth electro water station. After the GAP, came the ( peace pipes ) which began since the 1986, which is one of the most important subject in the Arabian Turkeys’ relations, despite his agricultural and development geodes to the region . The peace pipes project with provide water to the middle East states , and Gulf states, throw two pipeline, first, ( east line ) with 2700Km, and second ( east line ) or ( Gulf line ) with 3900Km. But it face may difficult in his way. The two project : GAP and peace pipes, have many objectives for Turkey, politically, economically, security etc.